Immunorelated gene polymorphisms associated with acute myeloid leukemia. (2nd June 2020) - Liu, Q.; Hua, M.; Yan, S.; Zhang, C.; Wang, R.; Yang, X.; Han, F.; Hou, M.; Ma, D.
Summary: Although the pathogenesis of acute myeloid leukemia (AML) is still unknown, accumulating evidence has revealed that immune response plays a vital part in the pathogenesis. Here, we investigated the involvement of 21 single nucleotide polymorphisms (SNPs) of immunorelated genes, including cytokines [interleukin (IL)‐2, IL‐4,  IL‐9, IL‐12A, IL‐22, interferon (IFN‐α) and transforming growth factor (TGF)‐β1], transcriptional regulatory genes ( TBX21, STAT1, STAT3, STAT5B, STAT6, GATA3, FOXP3 and IRF4 ) and others ( IL2RA,   IL6R, NFKBIA ) in 269 AML in‐patients and 200 healthy controls. Furthermore, we analyzed the relationship between the SNPs and clinical characteristics. Immunorelated SNP genotyping was performed on the Sequenom MassARRAY iPLEX platform. All the SNPs in healthy controls were consistent with Hardy–Weinberg equilibrium. All final P ‐values were adjusted by Bonferroni multiple testing. Our results showed that IL‐22 (rs2227491) was significantly associated with the white blood cell (WBC) counts. Signal transducer and activator of transcription 5B (STAT‐5B) (rs6503691) showed a close relationship with the recurrent genetic abnormalities in patients with AML. We verified the negatively independent effect of age and risk of cytogenetics on overall survival (OS). More importantly, the GG genotype of IL‐12A (rs6887695) showed a negative impact on AML prognosis independently. Furthermore, the relative expression of IL‐12 was decreased in GG genotype, no matter under a co‐dominant or recessive model. However, no correlation was observed between the SNPs mentioned above and disease susceptibility, risk stratification and survival. Our findings suggest that immunorelated gene polymorphisms are associated with prognosis in AML, which may perform as novel inspection targets for AML patients. Abstract : We investigated 21 single‐nucleotide polymorphisms (SNPs) of immunorelated genes in AML patients, no correlation was observed between the SNPs and disease susceptibility, risk stratification, and survival. But we found that IL22 (rs2227491) and STAT5B (rs6503691) were, respectively, significantly associated with high white blood cell count and the recurrent genetic abnormalities in AML patients. The GG genotype of IL12A (rs6887695) decreased the relative expression of IL12 and showed a negative impact on AML prognosis independently